MORPHOMETRIC ANALYSIS OF DUODENAL BIOPSIES IN PATIENTS WITH SUSPECTED COELIAC DISEASE - Stanković, Milica; Ilić, Ivan; Jovanović, Ivan; Stojanović, Nikola; Ugrenović, Slađana; Milićević, Aleksandar; Lazarević, Milica (Acta medicae Medianae, 2024)
Coeliac disease (CD) is an immune-mediated systemic disorder mostly presented in the form of small intestine enteropathy caused by gluten and related prolamins intake, from cereals such as wheat, barley, and rye. The diagnosis of CD is currently based on clinical presentation, pathohistological evaluation of the small intestine biopsies and positive serology. The aim of our study was to investigate histological abnormalities in the villous architecture of the duodenal bulb and postbulb segment in patients diagnosed with CD and in those biopsies sent for examination but the diagnosis was not confirmed. Morphometric analysis was performed on 35 duodenal samples obtained from patients with the initial clinical diagnosis of CD while some patients had dyspepsia as a primary diagnosis. The obtained data of villus width measured in the bulbar and postbulbar part of the duodenum were found to be statistically significantly different (p = 0.0226). The width of the duodenal villi in the bulbar part was significantly thicker than the one in the postbulbar part, while the value of the villous height at the examined places was not statistically significant. Also, none of the cases in this study showed any extensive abnormalities in villous architecture. Besides pathohistological examination which remains the gold standard in diagnosing, morphometric analysis may also be helpful in the detection of the latent forms of this entity. Having in mind that the chronic persistence of this disease may indicate various systemic dysfunction, long-term follow-up of these patients is necessary.